Penerapan Model Problem Based Learning dalam Pembelajaran Tematik Sekolah Dasar Guna Meningkatkan Keaktifan Siswa - Reno Septianingsih; Indah Putri Yani; Tantri Pramadita; Irawan Sukma; Mahilda Dea Komalasari (STIKes Ibnu Sina Ajibarang, 2024)
Thematic learning is learning that involves several scientific disciplines and is packaged in one theme. This research was conducted to explain teaching and learning methods in thematic learning. Implementation of the Problem Based Learning model, namely a learning model that exposes students to concrete problems in life while studying. Then students can relate the problem to the material to be studied. The application of the problem-based learning method forces students to carry out their own learning and actively explore students' information, to present problems and develop their own knowledge. It is hoped that using this based model will help students think critically and participate actively in the learning process. The research method used is literature study to perfect the analysis from the various sources used. So the results show that thematic learning using the Problem Based Learning model is able to increase student activity in learning